(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2025)
Introduction. In today’s dynamic market environment—characterized by intense competition, business digitalization, and rapidly changing consumer needs—marketing has acquired new strategic significance. Effective management of marketing projects requires precise coordination, accurate planning, decision-making flexibility, and continuous market data analysis. Under these conditions, the application of modern information technologies (IT) becomes especially relevant as tools for enhancing the efficiency of marketing strategies and campaigns. The purpose of the article. The purpose of this article is to investigate the capabilities and features of applying modern information technologies at different stages of marketing project management, to identify their advantages, potential risks, and development prospects within the context of business digital transformation. Methods. A comprehensive approach was applied, combining elements of theoretical analysis, comparative methodology, and practical principles of marketing project management using information technologies. The theoretical foundation comprised a systematic review of domestic and international scientific literature on marketing management, IT solutions, and agile project management methodologies (Agile, Scrum, PMBOK). To ensure a justified selection of IT tools at each of the five key stages of a marketing project’s life cycle, the method of criteria-based selection of IT instruments by functional correspondence was employed. Results. The study confirms that modern marketing project management is impossible without the implementation of information technologies, which fundamentally transform approaches to planning, execution, control, and performance evaluation of marketing campaigns. IT tools not only automate individual processes but also create new paradigms for communication, decision making, analytics, and stakeholder interaction. At each stage of the marketing project life cycle, specific IT solutions provide decision support, execution speed, and management transparency. Initiation: CRM systems (HubSpot, Zoho CRM) and market-research instruments (Google Trends, SEMrush, Ahrefs) systematically collect and analyze consumer and competitive data, while BI platforms (Power BI, Tableau) visualize correlations that underpin project concept development and feasibility assessment. Planning: Project management systems (Jira, Asana, ClickUp) generate structured backlogs and roadmaps in line with Agile principles, budgeting tools (Microsoft Excel, Smartsheet, Wrike) automate cost modeling, and visual platforms (Miro, MindMeister) align strategic goals with stakeholders. Execution: Digital-campaign platforms (Google Ads, Meta Ads Manager, TikTok Ads) adapt targeting and budget in real time; CMS solutions (WordPress, Webflow) streamline content delivery; marketing automation platforms (Mailchimp, GetResponse) handle complex communication funnels; and corporate communication tools (Slack, Microsoft Teams) integrate distributed teamwork. Monitoring and Control: Analytical platforms (Google Analytics, Facebook Pixel, Hotjar) capture behavioral metrics; reporting tools (Looker Studio, Power BI) produce real-time dashboards; KPI monitoring systems (KPI Fire, Grow.com) automate variance analysis and trigger corrective actions. Closure and Evaluation: Reporting and presentation packages (PowerPoint, Canva) standardize findings; feedback platforms (SurveyMonkey, Typeform) collect qualitative assessments; and knowledge-management systems (Notion, Confluence) consolidate best practices and lessons learned. Conclusions. Information technologies significantly enhance the efficiency of marketing project management by automating operations, centralizing data storage, and enabling real-time analysis of key performance indicators. The implementation of CRM systems, BI platforms, and modern project management tools reduces time and resource expenditures while increasing the speed and quality of decision making. Moreover, the adoption of Agile-oriented project management systems empowers marketing teams to respond swiftly to shifts in consumer demand and competitive landscapes.